2011
DOI: 10.1186/1472-6890-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-binding domain protein-based DNA isolation from human blood serum combines DNA analyses and serum-autoantibody testing

Abstract: BackgroundCirculating cell free DNA in serum as well as serum-autoantibodies and the serum proteome have great potential to contribute to early cancer diagnostics via non invasive blood tests. However, most DNA preparation protocols destroy the protein fraction and therefore do not allow subsequent protein analyses. In this study a novel approach based on methyl binding domain protein (MBD) is described to overcome the technical difficulties of combining DNA and protein analysis out of one single serum sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…The elevated cfDNA levels, however, were included as a separate predictor with in the study. Such an increase of cfDNA was frequently observed for diverse cancers Wielscher et al, 2011 , Jung et al, 2004 , Dawson et al, 2013 and late stage COPD patients Gormally et al, 2004 . The presence of DNA exhibiting disease marks in serum may be due to an interplay of several mechanisms Schwarzenbach et al, 2011 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The elevated cfDNA levels, however, were included as a separate predictor with in the study. Such an increase of cfDNA was frequently observed for diverse cancers Wielscher et al, 2011 , Jung et al, 2004 , Dawson et al, 2013 and late stage COPD patients Gormally et al, 2004 . The presence of DNA exhibiting disease marks in serum may be due to an interplay of several mechanisms Schwarzenbach et al, 2011 .…”
Section: Discussionmentioning
confidence: 59%
“…Standard curves, which also served as amplification control, as well as additional negative controls, were introduced before multiplexed enrichment. cfDNA was isolated out of 400 μl patients' serum using Roche High pure template preparation kit (Roche) with a modified isolation protocol published previously Wielscher et al, 2011 . In a volume of 12 μl cfDNA was digested with four methylsensitive restriction enzymes (MSRE) namely HpaII (ThermoFisher), Hin6I (ThermoFisher), AciI (NewEnglandBiolabs) and HpyCHIV4 (NewEnglandBiolabs).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally a combination of enrichment methods (e.g. by MBD-proteins) and MSRE based methylation detection may increase the sensitivity of qPCR results [20].…”
Section: Quantitative Dna Methylation Analysis With Methylation Sensimentioning
confidence: 99%
“…37,38 Several recent studies have demonstrated methylated DNA purification techniques using the methyl-binding protein (MBD) in solution phase in a wide array of human fluid samples. [37][38][39][40][41] These studies used the MBD protein as a capture molecule for directly and specifically binding the double-stranded methylated DNA in either a nanofluidic device or in use of magnetic beads, but not in the solid phase. For most techniques for methylated DNA purification that have been developed, the purification step was too complicated, time-consuming, and high-cost because of the use of additional molecules such as proteins and antibodies in solutionphase-based methods.…”
Section: Verification Of Dma Technique Via Genetic and Epigenetic Ana...mentioning
confidence: 99%